2007
DOI: 10.1016/j.jpainsymman.2006.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Forgoing Artificial Nutrition or Hydration in Patients Nearing Death in Six European Countries

Abstract: Whether or not artificial nutrition or hydration (ANH) may be forgone in terminally ill patients has been the subject of medical and ethical discussions. Information about the frequency and background characteristics of making decisions to forgo ANH is generally limited to specific clinical settings. The aim of this study was to compare the practice of forgoing ANH in six European countries: Belgium, Denmark, Italy, The Netherlands, Sweden, and Switzerland. In each country, random samples were drawn from death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 29 publications
7
33
0
1
Order By: Relevance
“…Those issues have been studied in several countries [1][2][3][4][5]. For example, in Holland, in a famous study sponsored by the Dutch government [2] on acts that terminate life, it was observed that the administration of drugs in lethal doses without explicit request from the patients occurred in 0.8% of all deaths.…”
Section: Symptom Controlmentioning
confidence: 99%
“…Those issues have been studied in several countries [1][2][3][4][5]. For example, in Holland, in a famous study sponsored by the Dutch government [2] on acts that terminate life, it was observed that the administration of drugs in lethal doses without explicit request from the patients occurred in 0.8% of all deaths.…”
Section: Symptom Controlmentioning
confidence: 99%
“…10 Few studies have described the range of CDs for this population, and most focused on specific decisions. 11,12 Little is known about the purposes of this kind of decisions for patients with advanced dementia. However, some papers [13][14][15][16][17] analyzed end-of-life decisions in different countries retrospectively interviewing the physicians who had cared for the deceased person.…”
Section: Introductionmentioning
confidence: 99%
“…The first result reported was that Italian doctors had the least experience in end-of-life decisions in comparison with colleagues of other European countries; this is probably due to the absence of definite rules not only about attending to a dying person but also with regard to donor transplantation and in general to the value of a patient's autonomy in such situations [37][38][39]. According to these observations, our preliminary data emphasized that decisions regarding patients on life-sustaining treatment is a controversial topic in Italy.…”
Section: Discussionmentioning
confidence: 99%
“…Onwuteaka-Philipsen pointed out that, in Italy, the sanctity of life is considered more important than quality of life, and patients would be reluctant to request withholding and withdrawing therapy because they may be influenced by the negative opinion of physicians regarding such a decision [48]. The reason given was that ''this would presumably upset the public opinion'' [36,39]. Giannini also underscored this point.…”
Section: Discussionmentioning
confidence: 99%